2001
DOI: 10.1099/00207713-51-2-667
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of 16S rRNA sequence similarity to DNA hybridization in prokaryotes.

Abstract: The relationship between 16S rRNA sequence similarity (S) and the extent of DNA hybridization (D) was well described by the equation ln(NlnD) l 053 [ln(NlnS)]M2201 when D was determined by either the S1 nuclease or membrane filter methods. When the presence of nonultrametric rRNA sequences and differences between genera or families were controlled, this relationship accounted for 78 % of the variability of D given S, and it was possible to estimate the distribution of D from S with a known precision. Thus, D T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
102
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 92 publications
7
102
0
1
Order By: Relevance
“…There is general agreement that a DNA-DNA relatedness level of approximately 70 % is the threshold value for defining species (Wayne et al, 1987). On the basis of the available data, organisms that share less than 97.0 % 16S rRNA gene sequence similarity will not show more than 60 % reassociation, irrespective of the hybridization method used (Stackebrandt & Goebel, 1994;Keswani & Whitman, 2001). Thus, the phylogenetic results for strain Gsoil 954 T demonstrated that the strain was not related to any of the recognized members of the genus Microlunatus.…”
mentioning
confidence: 99%
“…There is general agreement that a DNA-DNA relatedness level of approximately 70 % is the threshold value for defining species (Wayne et al, 1987). On the basis of the available data, organisms that share less than 97.0 % 16S rRNA gene sequence similarity will not show more than 60 % reassociation, irrespective of the hybridization method used (Stackebrandt & Goebel, 1994;Keswani & Whitman, 2001). Thus, the phylogenetic results for strain Gsoil 954 T demonstrated that the strain was not related to any of the recognized members of the genus Microlunatus.…”
mentioning
confidence: 99%
“…1). A similarity of less than 98 % in a 16S rRNA gene sequence is generally considered evidence for separate species (Keswani & Whitman, 2001). Furthermore, deduced amino acid sequences from mcrA gene analyses showed 89 % similarity between all the isolated strains and Table 1.…”
mentioning
confidence: 99%
“…In addition, the blots were stripped and rehybridized with a PCR amplicon from the 16S rRNA gene as the new probe, as described by Domenech et al (1997). This procedure has several advantages compared to previous methods (Keswani & Whitman, 2001), mainly because the amount of DNA fixed in each dot can be determined by measuring the amount of radioactivity when using the 16S rRNA gene as the second probe. Due to the high sequence conservation within mycobacterial species inherent within this probe (Menendez et al, 2002), the radioactivity level can be considered to be proportional to the amount of target molecules on the filter.…”
mentioning
confidence: 99%